Motility of sturgeon spermatozoa can sustain successive activations episodes - Dzyuba, B; Cosson, J; Boryshpolets, S; Dzyuba, V; Rodina, M; Bondarenko, O; A Shaliutina; Linhart, O (Animal reproduction science, 2013)
Here we report for the first time the possibility of sequential sperm motility activation in sturgeon (sterlet, Acipenser ruthenus), a fish with external fertilization, through changes either in osmolality (global solute concentration) or in the Ca(2+) concentration of the medium surrounding the spermatozoa. Sperm motility was initiated in any of three solutions containing buffer and sucrose at 80, or 40 or 10mM (called S80, S40, S10, respectively); S80 is hypertonic relative to sterlet seminal fluid, while S40 is isotonic and S10 is hypotonic. After cessation of sperm movement at the end of this first motility period, a second and then a third, subsequent motile phase were observed. The second motility period was induced at cessation of motility in S80 by imposing a two-fold decrease in osmolality. After arrest of motility in this half-diluted S80, a third motility period could be initiated by addition of CaCl2 to 1mM final concentration. At the end of a first motility period in either S40 or S10, subsequent motility re-activation episodes were achieved only by addition of 1mM CaCl2. Depending on conditions in which sperm samples were activated, significant differences in curvilinear velocity, percent motile spermatozoa, motility duration time, and specific external features of spermatozoa flagella were observed. Altogether, these observations on the ability of sturgeon spermatozoa to sustain sequential activation episodes by experimental adjustment of their environmental conditions represent a potent model for deeper investigations on the sperm motility activation mechanisms.
Keywords: osmolární koncentrace; Semen; Egtazic Acid; EGTA; Sperm Capacitation; Sperm Motility; vápník; mužské pohlaví; Osmolar Concentration; Calcium; zvířata; kapacitace spermií; sperma; motilita spermií; Fishes; ryby; Spermatozoa; spermie; Male; Animals